1988
DOI: 10.1111/j.1365-2362.1988.tb01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of collagen mRNA in normal and scleroderma skin by in‐situ hybridization

Abstract: Scleroderma is a fibrotic disease occurring in a localized or systemic form. Disturbed regulation of connective tissue metabolism plays an important role in its pathogenesis. However, until now, most of the data available were obtained from studies of fibroblasts in culture and there is considerable doubt that fibroblasts in a monolayer reflect the in-vivo situation. Using in-situ hybridization with specific antisense RNAs on frozen sections of skin, cells were detected displaying enhanced messenger RNA levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(85 citation statements)
references
References 30 publications
7
78
0
Order By: Relevance
“…First, it lacks the vascular and inflammatory lesions of human scleroderma (Jimenez 1988). Second, in human scleroderma there is an increase in the number of high collagen-producing fibroblasts compared with age-matched skin (Kahari et al 1988;Scharffetter et al 1988). In contrast, the onset of Tsk fibrosis coincides with a large number of high collagen-expressing fibroblasts in normal dermis, which is not properly reduced in Tsk thereafter (Pablos et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it lacks the vascular and inflammatory lesions of human scleroderma (Jimenez 1988). Second, in human scleroderma there is an increase in the number of high collagen-producing fibroblasts compared with age-matched skin (Kahari et al 1988;Scharffetter et al 1988). In contrast, the onset of Tsk fibrosis coincides with a large number of high collagen-expressing fibroblasts in normal dermis, which is not properly reduced in Tsk thereafter (Pablos et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The transcription of procollagen genes in fibroblasts of normal and fibrotic skin is uneven. In both circumstances, heterogeneity in the amount of procollagen mRNA or collagen synthesis in fibroblasts can be observed by in situ hybridization or in vitro cloning of fibroblasts (Goldring et al 1990; Kahari et al 1988;Scharffetter et al 1988;Fleischmajer et al 1981). The hallmark of scleroderma is the presence of an expanded subpopulation of fibroblasts containing high levels of procollagen mRNA.…”
mentioning
confidence: 99%
“…35,36 In healthy skin, the majority of the cells with fibroblastic morphology, as well as endothelial cells in deep dermis, express Fli1 ( Figure 6, a and b). In contrast, in clinically involved skin of SSc patients with active disease, Fli1-positive fibroblasts were either absent or only occasionally seen.…”
Section: Fli1 Is Underexpressed In Ssc Skin In Vivomentioning
confidence: 99%
“…(iii) Fibroblasts adjacent to dermal inflammatory infiltrate rich in T cells and monocytes show enhanced synthesis of collagen when studied by in situ hybridization This article is a contribution to the Special Issue on Immunopathology of Systemic Sclerosis -Guest Editors: Jacob M. van Laar and John Varga [29,47,100]. (iv) Genome-wide association studies, which are intrinsically unbiased, have identified several polymorphisms conferring susceptibility to SSc located, in the large majority, within gene relevant fore innate and adaptive immune responses [2,14,39,40,71,85].…”
Section: Introductionmentioning
confidence: 99%